THE INTEGRATED MARKETING BLUEPRINT: ALIGNING BRAND, CONTENT, AND SALES FOR MAXIMUM IMPACT - Desy Afriyanti; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
In an increasingly fragmented digital landscape, organizations often deploy brand, content, and sales strategies in functional silos, leading to inconsistent customer experience and suboptimal resource allocation. This research addresses the critical need for a unified framework to synchronize these core marketing functions. The objective was to develop and validate a practical blueprint for integrated marketing that enhances strategic alignment and measurable impact. The methodology employed a qualitative multi-case study analysis of five B2B and B2C companies recognized for marketing excellence, supplemented by in-depth interviews with senior marketing leaders. The results reveal that successful integration is predicated on a shared customer-value narrative, cross-functional governance, and unified performance metrics. The discussion underscores that this alignment transforms content into a strategic asset for both brand building and sales acceleration, fostering a cohesive customer journey. In conclusion, the proposed Integrated Marketing Blueprint provides a actionable model for breaking down internal silos. Its adoption is shown to increase marketing ROI, improve customer lifetime value, and drive sustainable growth by ensuring every customer touchpoint is strategically coherent.